Degradasi Karet Alam Menggunakan Katalis CoCl2 Dengan Variasi Waktu Reaksi - Ivan Fadhillah; Said Zul Amraini; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Liquid Natural Rubber (LNR) is a product of natural rubber latex depolymerization process whose molecular weight specifications are influenced by several factors. Two of them are CoCl2 catalyst content and depolymerization reaction time. This study aims to synthesize Liquid Natural Rubber (LNR) from Latex Natural Rubber and determine the effect of variations in the addition of CoCl2 catalyst levels and reaction time to the molecular weight of the resulting LNR. The first treatment in this study had several stages, namely the preparation of raw materials including dilution of natural rubber latex resulting from cutting of rubber trees into natural rubber latex with dry rubber content (DRC) 20%. After that, the process of depolymerization was continued with the help of a CoCl2 catalyst which varied the levels of CoCl2 1 phr, reaction times 7, 8 and 9 hours, stirring speed of 250 rpm and stirring temperature of 70 ºC. The final stage of LNR purification was using methanol, toluene and oven at a temperature of 70ºC. The LNR products obtained are liquid and semi-gel. The formed LNR has functional groups and structures that conform to the LNR formation specifications. While the Mn LNR molecular weight value with a variation of ,reaction time, did not experience a significant difference for each additional reaction time.Keywords : liquid natural rubber, gel permeation chromatography, cobalt dichlorite, depolymerization and dried rubber crumb.